Pathomechanism of Renal Damage in Type 2 Diabetes Mellitus Patients - Yuliana Sambara; Mansyur Arif; Uleng Bahrun (The Prodia Education and Research Institute (PERI), 2013)
BACKGROUND: Hyperglycemia in diabetic patients cause both chronic inflammation and extracellular matrix accumulation that can lead to progressive renal damage. Albumin, Gammaglutamytransferase (GGT) and clusterin in urine are markers to detect damage in glomerulus, cell of the tubules and proximal tubules, respectively.METHODS: This study aimed to evaluate the pathomechanism of haemoglobin A1c (HbA1c), albumin, GGT, clusterin, type IV collagen in urine, and high sensitivity C-reactive protein (hsCRP) in type 2 diabetes mellitus (DM) patients. The study was a cross sectional study involving 82 subjects consisting of 36 males and 46 females, 35-65 years old, divided into 3 groups: uncontrolled DM, controlled DM and non DM. Data were obtained from interviews, physical examinations (weight, height, blood pressure) and laboratory examinations (HbA1c, serum glutamic oxaloacetic (SGOT), serum glutamic pyruvic (SGPT), creatinine, hsCRP, urinary albumin, urinary GGT, urinary clusterin, and urinary type IV collagen). Statistical analysis was performed for correlation, difference and cross tabulation tests.RESULTS: The study results showed there were significant differences (p<0.05) between uncontrolled DM group compared with controlled DM and non DM groups in HbA1c, ratio of urinary type IV collagen and ratio of urinary albumin. However, there were no significant differences between controlled DM and non DM groups. There were positive significant correlations between HbA1c with hsCRP (r=0.223, p<0.05), HbA1c with ratio of urinary type IV collagen/creatinine (r=0.563, p<0.001), HbA1c with ratio of urinary albumin/creatinine (r=0.263, p<0.05), and ratio of urinary type IV collagen/creatinine with ratio urinary albumin/creatinine (r=0.613, p<0.001).CONCLUSION: Results of this study indicated that albumin and type IV collagen in urine play a role in renal damage caused by uncontrolled glucose level in subjects with type 2 DM. The increased concentration of both HbA1c and urinary type IV collagen indicates increased risk factor of glomerulus damage. Urinary type IV collagen is likely to be future potential marker for early detection of renal damage.KEYWORDS: renal damage, HbA1c, hsCRP, type IV collagen, GGT, clusterin, diabetes mellitus